Acaricidal activity of essential oil nanoemulsion against the African red mite (Eutetranychus africanus) - Thanaporn Doungnapa; Jarongsak Pumnuan; Ammorn Insung (My University, 2021)
The African red mite (Eutetranychus africanus [Tucker]) is an important pest species of some economic plants. The objective of the present study was to evaluate the effectiveness of nanoemulsions consisting of citronella grass, lemongrass, clove, and cinnamon essential oils and their main chemical compounds against the African red mite; their toxicity, egg-laying inhibition, and repellent effect on the mite were determined. Essential oil nanoemulsions (nEOs) were prepared by mixing the essential oils with different surfactants and co-surfactants. Approximately 10 to 15 female mites were transferred to treated leaves placed on soaked cotton and kept in a Petri dish. Mite mortality and number of eggs laid were checked after 24 h. As for the repellency test, the selected test consisted of dipping a half leaf into the nEOs, while the other half leaf was dipped in a control (water). The repellency rate was evaluated after 24 h. Results revealed that citronella grass nEOs exhibited a highly toxic effect on the mite and only a 0.6% concentration caused 100% mite mortality. Geraniol, one of the main chemical compounds of citronella grass, represented the highest egg-laying inhibition at a 0.2% concentration with a mean of 0.1 egg compared with 4.7 eggs in the control. Furthermore, nEOs from citronella grass at a 0.1% concentration were extremely repellent against the mite with 95% repellency after 24 h. Therefore, the citronella grass essential oil nanoemulsion is appropriate for use to effectively control the African red mite.
Keywords: Insect Pest Control Strategies